Robust Action and the Rise of the Medici - Padgett, John F.; Ansell, Christopher K. (The American Journal of Sociology, 1993)
Ẅe analyze the centralization of political parties and elite networks that underlay the birth of the Renaissance state in Florence. Class revolt and fisical crisis were the ultimate causes of elite consolidation, but Medicean political control was produced by means of network disjunctures within the elite, which the Medici alone spanned. Cosimo de' Medici's multivocal identity as sphinx harnessed the power available in these network holes and resolved the contradiction between judge and boss inherent in all organizations. Methodologically, we argue that to understand state formation one must penetrate beneath the veneer of formal institutions, groups, and goals down to the relational substrata of peoples' actual lives. Ambiguity and heterogeneity, not planning and self- interest, are the raw materials of which powerful states and persons are constructed.We analyze the centralization of political parties and elite networks that underlay the birth of the Renaissance state in Florence. Class revolt and fisical crisis were the ultimate causes of elite consolidation, but Medicean political control was produced by means of network disjunctures within the elite, which the Medici alone spanned. Cosimo de' Medici's multivocal identity as sphinx harnessed the power available in these network holes and resolved the contradiction between judge and boss inherent in all organizations. Methodologically, we argue that to understand state formation one must penetrate beneath the veneer of formal institutions, groups, and goals down to the relational substrata of peoples' actual lives. Ambiguity and heterogeneity, not planning and self- interest, are the raw materials of which powerful states and persons are constructed.\"[Häberlein 2008, S. 327]Die Autoren ẅeisen auf hohem mehtodologischen Niveau die Bedeutung sozialer Netzwerke für die Konstituierung der Medici-Herrschaft im Florenz des 15. Jahrhunderts\" nach [usw.]
Keywords: Medieval History